The Impact of Malnutrition on Perioperative Ischemic Stroke in Transcatheter Aortic Valve Replacement (TAVR): A Retrospective Cohort Study of the National Inpatient Sample - Haowei Li; Guangzhi Cong; Xueping Ma; Bo Shi; Congyan Ye; Rui Yan; Shizhe Fu; Kairu Wang; Shaobin Jia; Jingjing Wang (Health Science Reports)
ABSTRACT Background and Aims Ischemic stroke is a serious risk for patients undergoing transcatheter aortic valve replacement (TAVR). The relationship between malnutrition and post‐TAVR ischemic stroke remains unclear. This study investigates this association using the National Inpatient Sample (NIS) data. Methods A retrospective observational study was conducted using NIS data from 2012 to 2021. We included patients who underwent TAVR and were diagnosed with malnutrition based on ICD‐9 and ICD‐10 codes. Patients under 18 years, with a history of preoperative stroke, with both ischemic and hemorrhagic strokes, or with incomplete data were excluded. Logistic regression was performed to evaluate the association between malnutrition and ischemic stroke, adjusting for potential confounders. Sensitivity analyses included stratified analysis and propensity score matching. Results Among 364,580 TAVR patients, 10,415 (2.86%) were diagnosed with malnutrition. Malnourished patients were older (78.04 vs. 77.40), predominantly white (85.69%), and had a higher incidence of ischemic stroke (11.47% vs. 7.25%, p < 0.001). After adjusting for common ischemic stroke risk factors, malnutrition was significantly associated with an increased risk of ischemic stroke (aOR: 1.51; 95% CI: 1.31–1.74). This association remained significant in the propensity‐matched cohort. Subgroup analyses consistently showed associations between malnutrition and stroke risk across various demographic and clinical factors. Time trend analysis showed no significant difference in the annual incidence of perioperative ischemic stroke between malnourished patients with or without cerebral embolic protection devices (p = 0.439). Conclusion Malnutrition is associated with a higher risk of ischemic stroke following TAVR, highlighting the need for targeted interventions.